(untitled) (Journal of Asian Development Studies, 2024)
Emotion regulation plays a pivotal role in understanding the complex relationships between personality traits and aggressive behavior. This study examined the mediating role of emotion regulation in the relationships between personality traits and aggression among university students. A correlational research design was employed and convenience sampling technique was used, with a sample of 190 students from the Institute of Southern Punjab, Multan. Participants completed the Big Five Inventory (BFI-10) which was invented by John et al. (1991), the difficulties in emotion regulation scale-16 that was developed by (Bjureberg et al., 2016) and the 12- item Brief Aggression Questionnaire (BAQ) developed by Webster et al. (2014). The results revealed significant positive correlations between extraversion (r =.46**, p< .001), neuroticism (r = .48**, p< .001), difficulties in emotion regulation (r = .342**, p< .001) showed a negative correlation with aggression. Regression analysis demonstrated that difficulties in emotion regulation significantly mediate the relationship between personality traits and aggression with a R² value of .117. These results suggest that emotion regulation plays a critical role in mitigating aggression, especially in individuals high in neuroticism and extraversion. The study highlights the importance of fostering emotional well-being through interventions aimed at improving emotional regulation in university settings, which may reduce aggression and promote a healthier campus environment. Future research should focus on diverse samples and longitudinal designs to confirm these findings.